Criminal minds. The eleventh season [videorecording (DVD)] - Davis, Jeff, 1975- (Criminal minds (Television program), 2016)
The FBI's Behavioral Analysis Unit braves a relentless enemy that jeopardizes their professional lives and demands unprecedented personal sacrifices. Tackling a network of cunning, cutthroat hitmen linked by the Darknet, Special Agents Aaron Hotchner, David Rossi, Derek Morgan, Jennifer JJ Jareau, Dr. Spencer Reid, technical analyst Penelope Garcia, and a new crew member, forensic psychologist Dr. Tara Lewis, delve into the depths of the Dark Web, and put their lives in peril like never before.